Vocational Schooling, Labor Market Outcomes, and College Entry - Chen, Dandan (2012)
This paper examines the differentiated outcomes of vocational and general secondary academic education, particularly in terms of employment opportunities, labor market earnings, and access to tertiary education in Indonesia. With data from a panel of two waves of the Indonesia Family Life Survey in 1997 and 2000, the paper tracks a cohort of high school students in 1997 to examine their schooling and employment status in 2000. The findings demonstrate that: (1) attendance at vocational secondary schools results in neither market advantage nor disadvantage in terms of employment opportunities and/or earnings premium; (2) attendance at vocational schools leads to significantly lower academic achievement as measured by national test scores; and (3) There is no stigma attached to attendance at vocational schools that results in a disadvantage in access to tertiary education; rather, it is the lower academic achievement associated with attendance at vocational school that lowers the likelihood of entering college. The empirical approach of this paper addresses two limitations of the existing literature in this area. First, it takes into account the observation censoring issue due to college entry when evaluating labor market outcomes of secondary school graduates. Second, using an instrumental variable approach, the paper also treats endogeneity of household choice of vocational versus academic track of secondary education, teasing out the net effect of secondary school choice on labor market and schooling outcomes.